2021
DOI: 10.1108/jeim-11-2020-0461
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cloud computing assimilation on supply chain financing risks of SMEs

Abstract: Purpose The purpose of this study is to examine how cloud computing assimilation reduces supply chain financing (SCF) risks of small and medium enterprises (SMEs). This study also investigated the mediating roles of internal and external supply chain integration between cloud computing assimilation and the SCF risks of SMEs, as well as the moderating role of environmental competitiveness. Design/methodology/approach Data was collected from surveys of SMEs located in China.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 105 publications
2
39
0
Order By: Relevance
“…Similarly, Liao et al (2021) investigated the relationship between SCI and supply chain capability and performance in Taiwanese lifts, with the degree of integration found to be a mediating variable with a moderating effect. Lu et al (2021) examined the mediating effect of internal and external integration of SCI on cloud assimilation and supply chain financing risk of small and medium enterprises. Empirical studies demonstrated that cloud assimilation can reduce the supply chain financing risk of small and medium enterprises.…”
Section: Knowledge Trajectory Of Supply Chain Integrationmentioning
confidence: 99%
“…Similarly, Liao et al (2021) investigated the relationship between SCI and supply chain capability and performance in Taiwanese lifts, with the degree of integration found to be a mediating variable with a moderating effect. Lu et al (2021) examined the mediating effect of internal and external integration of SCI on cloud assimilation and supply chain financing risk of small and medium enterprises. Empirical studies demonstrated that cloud assimilation can reduce the supply chain financing risk of small and medium enterprises.…”
Section: Knowledge Trajectory Of Supply Chain Integrationmentioning
confidence: 99%
“…Li, Sun and Wu (2019) used cloud computing technology to improve the logistics distribution planning of coastal ports. Lu et al (2021) conducted a study in which they addressed reducing the risks of the financing supply chain using cloud computing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The virtual reality user is fully involved in an artificial environment and has no interaction with the surrounding real world. However, augmented reality allows the user to see and interact with the real world and virtual Cañas et al, 2020;Kaya et al, 2020;Mostafa et al, 2019;Ramirez-Peña et al, 2020;Rueda-Rueda & Portocarrero, 2021;Sharma et al, 2020;Sobb et al, 2020;Frederico, 2021b Connecting any physical object to the world wide web and identifying it in the virtual world Internet of Things (IoT) Cañas, Mula & Campuzano-Bolarín, 2020;Chen, Dui & Zhang, 2020;Kaya, Paksoy & Garza-Reyes, 2020;Martins, Simon & Campos, 2020;Ramirez-Peña et al, 2020;Sobb, Turnbull & Moustafa, 2020;Wang & Zhang, 2020;Frederico, 2021a Integrating all systems and subsystems and their monitoring and control Cyber-Physical Systems (CPS) Singh et al, 2015;Schniederjans, Ozpolat & Chen, 2016;Suherman & Simatupang, 2017;Li, Sun & Wu, 2019;Alam, 2020;Kaya, Paksoy & Garza-Reyes, 2020;Martins, Simon & Campos, 2020;Ramirez-Peña et al, 2020;Sobb, Turnbull & Moustafa, 2020;Lu et al, 2021 Calculating data and analysing, connecting and storing it in the network Cloud Computing Hofmann, 2017;Lamba & Singh, 2017;Raman et al, 2018;Cañas, Mula & Campuzano-Bolarín, 2020;Kamble & Gunasekaran, 2020;Kaya, Paksoy & Garza-Reyes, 2020;Martins, Simon & Campos, 2020;…”
Section: Virtual Realitymentioning
confidence: 99%
“…Scholars have confirmed that SCF brings financing conveniences to SMEs such as activates working capital (Liebl et al, 2016), promotes performance (Lu et al, 2020) and facilitates finance (Caniato et al, 2016). However, SCF also leads to risks to financial service providers (FSPs) and SMEs, namely supply chain financing risks (SCFR), which refers to the defaults of unable to repay on time or in full amount and the corresponding losses to FSPs caused by poor management or external environmental factors (Zhu et al, 2019;Lu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have developed to identify (Zhao et al, 2015), predict (Zhu et al, 2019), evaluate (Moretto et al, 2019) and mitigate SCFR (Lu et al, 2022). A key insight is that reducing SCFR is an important prerequisite for ensuring sustainable and healthy development of SCF, for SCFR greatly depresses the confidence and enthusiasm of FSPs to provide SCF and causing FSPs to suffer financial losses (Lu et al, 2022). Meanwhile, it can also lead to the decline of the credit level of SMEs and affect their subsequent external financing capacity, which may result in vicious circle (Song et al, 2020).…”
Section: Introductionmentioning
confidence: 99%